2012
DOI: 10.2319/061312-493.1
|View full text |Cite
|
Sign up to set email alerts
|

Does chlorhexidine in different formulations interfere with the force of orthodontic elastics?

Abstract: Objective: To evaluate the effects of different concentrations of chlorhexidine on the decline in force of orthodontic elastics. Materials and Methods: In a laboratory study, five groups of samples were tested, with one control group represented by distilled water (group 1) and four experimental groups: 0.12% manipulated chlorhexidine (group 2), 0.2% manipulated chlorhexidine (group 3), 0.12% chlorhexidine gluconate-based oral solution (0.12% Periogard; group 4), and 0.2% Cleanform mouthwash (formula and actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(75 citation statements)
references
References 15 publications
7
68
0
Order By: Relevance
“…The use of 0.12% chlorhexidine as a disinfecting agent has been proposed for base plates of removable orthodontic appliances, among other substrates 13 . A previous study suggested that chlorhexidine solutions in different concentrations have no significant influence on the force degradation of elastic chains 14 . However, the comparison of chlorhexidine and peracetic acid effects on force of elastic chains after disinfection remains not assessed.…”
Section: Introductionmentioning
confidence: 96%
“…The use of 0.12% chlorhexidine as a disinfecting agent has been proposed for base plates of removable orthodontic appliances, among other substrates 13 . A previous study suggested that chlorhexidine solutions in different concentrations have no significant influence on the force degradation of elastic chains 14 . However, the comparison of chlorhexidine and peracetic acid effects on force of elastic chains after disinfection remains not assessed.…”
Section: Introductionmentioning
confidence: 96%
“… 2 , 6 In several studies, including one conducted by Pithon et al, a 24-hour period was chosen since it generally constituted the time for elastic users to replace their elastics, while a 12-hour period represented the median time between initial use and replacement. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The present study occurred in a period of 4 weeks, because this is the time interval most frequently observed in orthodontic offices, with regard to consultations 1,21 . The size of elastic chains adopted in this study was the short elastic chain, considering that there are differences in the forces exerted by the segments of long and short chains, when stretched over the same distance, so that the segment of the short chain without space between the links has shown higher values of force over the course of time 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…This equipment was used in a previous study by Pithon et al 1 , to evaluate the influence of chlorhexidine on the force released by chain elastics. It should be pointed out that while the measurements were made, the room temperature was maintain constant at 25Cº.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation